The Viewpoints of Last-Year Dentistry Students of Shahid Beheshti University on the Application of Lasers as an Independent Credit in the Education of General Dentistry - Mehdipour, Masoumeh; Mortazavi, Hamed; Bahramian, Ayla; Haghighi Enayat, Niloofar; Azari-Marhabi, Saranaz (Journal of Lasers in Medical Sciences, 2020)
Introduction: Enhancing students’ pragmatic skills as an enabling means warrants changes in their curricula, which should be reconciled with the students’ educational needs. Thus, this study seeks to examine the viewpoints of last-year dentistry students on the need for the instruction of laser application as an independent credit in general dentistry curricula. The findings of this study can be helpful in determining the educational priorities of students while providing and compiling their curricula. Methods: This descriptive study was done on 91 last-year dentistry students of Shahid Beheshti University in a full census manner. The data collection tool was a fieldwork questionnaire which its validity and reliability evaluation was carried out. To announce the findings, frequency distribution, frequency percentage and average tableaux were utilized. Results: Amongst the 91 participants, regarding the average figures of value assignment from 1 to 10 to respond to questions, the highest value was assigned to learning the side effects of lasers (7.99 ± 0.01), and the lowest importance of and need for learning was assigned to learning about the history of laser and light physics (4.53 ± 0.47). Conclusion: The findings indicate that students have a positive attitude toward the incorporation of an independent laser credit in their curricula and, thus, the necessity of incorporating this credit in their curricula can be posed.